Socio-spatial segregation and housing in Brazil between late 19th and the early 20th century - Soares, Edmilson [UNESP]; Santos, Leandro Bruno (Univ Federal Espirito Santo, 2015)
This article aims to analysis the Brazilian city between late 19th and the early 20th century, when there are structural changes in the economic, social and political framework that will lead to new forms of production and consumption of the city and housing. It overlaps the archaic matrix of colonial trait a new guise that disguised as modern has only exacerbated their dramatic injustices, leading to production of a segregated urban space, both socially and space terms. The access to land and the State participation are central to the explanation of theses inequalities. The methodological procedures include bibliographic survey, selection and reading, data compilation, data and information systematization, data analysis. We conclude that, between late 19th and early 20th century, the Brazilian cities are the product of urbanization whose logic state intervention produced clear inequalities between sectors of the city, because it favored those spaces fitted with infrastructure at the expense of the shortage of rest of the city.
Keywords: Production of space; socio-spatial segregation; housing; Brazil